THE CONCEPTUAL FRAMEWORK OF EARLY CHILD MARRIAGE IN PAKISTANI SOCIETY - Salma Nawaz; Mouna Koser; Kanwal Bilal; Malik Shahzad Shabbir; Rabia Latif (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
Early Marriage or marriage in adolescence is characterized as marriage before attaining the age of 18 applies to both girls and boys; however, it is most usual among girls. Child marriage is a reality that prevails in numerous nations. The matter keeping in view its significance is not addressed for quite a long time and acknowledged or recognized as a standard. It is an emerging issue in Pakistan. The objective of this research was to analyze the situation of child marriages in Pakistan. The data was gathered from reports of non-government organizations, reports prepared by government authorities, different research papers and reports from newspapers. It was observed that poverty arises as significant reason affecting the early marriage circumstances in various ways viz a viz and especially the method of marriage. A portion of the significant causes are: Economic limitations because of poverty, safety of young girls, family honor, the aspect of child mortality, lower education and Illiteracy. It was concluded that and taking everything into account, early marriage is a worldwide issue and Pakistani ladies are casualties of this practice for a long time. Besides, there are numerous other issues like social, customary practices, prudent and religious variables that are adding to it. So it was recommended that government and non-government organizations should play their vital role and try to implement laws regarding the prevention of child marriages.